Early threat warning via speech and emotion recognition from voice calls - Ishtiak, Ifaz; Rahman, Mohammad Mazedur; Usmani, Md.Razaul Haque (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.